2018
DOI: 10.1016/j.carbpol.2018.06.067
|View full text |Cite
|
Sign up to set email alerts
|

Multistage extraction and purification of waste Sargassum natans to produce sodium alginate: An optimization approach

Abstract: Sargassum in the Caribbean region has affected the livelihood of several coastal communities due to the influx of large quantities of the seaweed in recent times. This article seeks to explore how waste Sargassum natans can be utilized to produce sodium alginate. The novelty in this research lies in the optimization process, whereby multistage extraction and precipitation were investigated over commonly used single stage processing, in an effort to maximize both yield and purity. The results showed that a maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 42 publications
(60 reference statements)
4
32
0
Order By: Relevance
“…This polysaccharide is one of the most versatile polymers, historically used in a wide ranges of industries (food, feed, textile printing, papermaking and pharmaceutical), and with more recent applications in the biomedical and bioengineering fields (Peteiro et al 2018). Interestingly, recent work using S. natans harvested in the Caribbean suggested that sodium alginate extracted from this species could be used as an alternative for packaging and encapsulation (Mohammed et al 2018), and calcium alginate could be considered as a successful biosorbent of heavy metals ions (Mohammed et al 2019).…”
Section: Determination Of Phenolic and Phlorotannin Contentmentioning
confidence: 99%
“…This polysaccharide is one of the most versatile polymers, historically used in a wide ranges of industries (food, feed, textile printing, papermaking and pharmaceutical), and with more recent applications in the biomedical and bioengineering fields (Peteiro et al 2018). Interestingly, recent work using S. natans harvested in the Caribbean suggested that sodium alginate extracted from this species could be used as an alternative for packaging and encapsulation (Mohammed et al 2018), and calcium alginate could be considered as a successful biosorbent of heavy metals ions (Mohammed et al 2019).…”
Section: Determination Of Phenolic and Phlorotannin Contentmentioning
confidence: 99%
“…Sodium alginate was detected in S. natans collected from both Manzanilla and Mayaro Bays (Trinidad). 70…”
Section: Sargassum Natansmentioning
confidence: 99%
“…The extraction of sodium alginate (Alg) was performed from Sargassum linifolium, using slightly modified protocols [ 21 , 43 ]. Briefly, collected seaweed biomass (100 g) was recurrently cleansed with DW, air-dried and soaked in 1 L of 2% formaldehyde solution for 14 h to eradicate pigments, then washed with DW and immersed in 0.2 M H 2 SO 4 solution (at 1:10 w/v ) before keeping for 2 h. Next, samples were further rinsed by DW and extracted with 5% Na₂CO₃ solution for 6 h under agitation.…”
Section: Methodsmentioning
confidence: 99%
“…Alginate (Alg) is the extracted hydrophilic polysaccharide from brown macroalgae. This linear biopolymer composition contains uronic acids, α-l-guluronic acid, and 1,4-linked-β-d-mannuronic acid [ 21 ]. Alg properties include non-toxicity, biodegradability, mucoadhesion and biocompatibility, which advocate its biomedical, nutraceutical, pharmaceutical and environmental applications [ 22 ].…”
Section: Introductionmentioning
confidence: 99%